X-ray/UV/optical variability of NGC 4593 with Swift: reprocessing of X-rays by an extended reprocessor. Issue 3 (2nd August 2018) - McHardy, I M; Connolly, S D; Horne, K; Cackett, E M; Gelbord, J; Peterson, B M; Pahari, M; Gehrels, N; Goad, M; Lira, P; Arevalo, P; Baldi, R D; et al.
ABSTRACT: We report the results of intensive X-ray, UV, and optical monitoring of the Seyfert 1 galaxy NGC 4593 with Swift . There is no intrinsic flux-related spectral change in any variable component with small apparent variations being due to contamination by a constant hard (reflection) component in the X-rays and the red host galaxy in the UV/optical. Relative to the shortest wavelength band, UVW 2, the lags of the other UV/optical bands mostly agree with the predictions of reprocessing of high energy emission by an accretion disc. The U -band lag is, however, larger than expected, probably because of reprocessed Balmer continuum emission from the distant broad line region (BLR). The UVW 2 band is well correlated with the X-rays but lags by ∼6× more than expected if the UVW 2 results only from reprocessing of X-rays by the disc. However, if the light curves are filtered to remove variations on time-scales >5 d, the lag approaches the expectation from disc reprocessing. memecho analysis shows that direct X-rays can be the driver of most of the UV/optical variations if the response functions have tails up to 10 d, from BLR reprocessing, together with strong peaks at short lag (<1 d) from disc reprocessing. For the 5 AGN monitored so far, the observed UVW 2 to V -band lags are _2 of disc reprocessing expectations and vary little between AGN. However, the X-ray to UVW 2 lags greatly exceed disc reprocessing expectations and differ between AGN. The two most absorbed AGN have the largest excesses, so absorption and scattering may affect these lags, but there is no simple relationship between excess and absorption.